Acta Medica Philippina in Dr. Florentino B. Herrera, Jr. Medical Library College of Medicine University of the Philippines Manila, 1982-2012 a citation analysis - Vinzon, Minette R. (School of Library and Information Studies, University of the Philippines Diliman, 2014)
The study analyzed the citations in the articles appended in Acta Medica Philippina, from 1982-2012. Specifically the study sought to: (a) determine the distribution of publication (type of document) such as journals, books, electronic sources, proceedings of conferences, seminars and meetings, reports and letters, theses/dissertations/unpublished materials used as reference in Acta Medica Philippina; (b) determine volume-wise distribution of citations; (c) study the authorship patterns in citations, and provide the most cited authors; (d) determine the age distribution of literature; (e) determine the obsolescence rate of periodical literature; (f) provide the most cited periodicals based on the frequency of use; (g) To determine the geographical (country-wise) distribution of literature, and; (h) determine the Journal Impact Factor of Acta Medica Philippina.